Comparison Study of Foreign Tourist Preferences in Choose The Attributes of Tourism Destination Pre and Post Natural Disaster - Arismayanti, Ni Ketut; Rahyuda, Irma (E-Journal of Tourism; Volume 7 Number 2 (September 2020)DO - 10.24922/eot.v7i2.64592, 2020)
Post natural disaster there is a shift in the atributs selection of tourism destinations. This research was conducted at a Bali tourism destination when Agung mountain natural disaster occurred. The background of the research objective to find out the preferences of overseas tourists, in choosing tourist destinations during their visit destinations by comparing the conditions of pre and post natural disasters. The types of data used in this study are qualitative and quantitative data. Data sources come from primary and secondary data. Data collection techniques by observation, interviews, questionnaires, documentation and literature. Data analysis techniques with descriptive statistics and conjoint analysis, sampling techniques with Slovin formulas for foreign tourists who have visited Bali pre and post natural disasters of Mount Agung eruption. This research findings that preferences of foreign tourists in the selection of tourist destinations before natural disasters are strongly influenced by low prices / special offers, but after natural disasters are greatly influenced by information or promotion in articles in magazines/newspapers and films when to choose tourism destinations. Keywords: preference, foreign tourist, natural disaster, tourism destination